2010
DOI: 10.3844/ajassp.2010.1057.1065
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Effects of Alkaloids Isolated from the Tuber of <i>Stephania venosa via</i> the Induction of Cell Cycle Arrest in Mammalian Cancer Cell Lines

Abstract: Approach:The research was carried out to extract, isolate, purify and elucidate structure of the active compound from the tuber S. venosa. Most of the solvent extracts and isolated compound were evaluated with kinds of mammalian cancer cell lines for investigation on antiproliferative effects. Results: Four alkaloids, tetrahydropalmatine (1), crebanine (2) O-methylbulbocapnine (3) and Nmethyltetrahydropalmatine (4) were isolated from the tuber of S. venosa. Charaterization of the compounds were carried out by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…Crebanine is an isoquinoline alkaloid found in several plants, including Stephania venosa, which is known in Thai as Sabuleud (Ingkaninan et al, 2006;Nantapap et al, 2010). The herbal extract from S. venosa has been widely used for a variety of indications in traditional Thai medicine (Likhitwitayawuid et al, 1993), yet the mechanism of therapeutic action of its alkaloids has not been well defined, especially in nerve tonic indications.…”
Section: Introductionmentioning
confidence: 99%
“…Crebanine is an isoquinoline alkaloid found in several plants, including Stephania venosa, which is known in Thai as Sabuleud (Ingkaninan et al, 2006;Nantapap et al, 2010). The herbal extract from S. venosa has been widely used for a variety of indications in traditional Thai medicine (Likhitwitayawuid et al, 1993), yet the mechanism of therapeutic action of its alkaloids has not been well defined, especially in nerve tonic indications.…”
Section: Introductionmentioning
confidence: 99%
“…Crebanine was isolated and purified from ethyl acetate fraction of the tube of Stephania vernosa as our previously described. 15,18) It was obtained as light yellow crystals, melting point at 117.0-117.8°C. The structure of crebanine was elucidated by extensive spectroscopic analysis (UV, IR, MS, 1 H-NMR,…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, CN has gained much attention due to its biological activities and proven pharmacological safety. 7,8) It was shown that CN more selectively decrease the survival and proliferation of cancerous cell lines than it does normal human fibroblasts.…”
Section: )mentioning
confidence: 99%
“…In recent years, CN has gained much attention due to its biological activities and proven pharmacological safety. 7,8) It was shown that CN more selectively decrease the survival and proliferation of cancerous cell lines than it does normal human fibroblasts. 9) Moreover, CN has anti-invasive property in cancer cells by inhibiting constitutive nuclear factor kappa B (NF-κB) activation.…”
mentioning
confidence: 99%
See 1 more Smart Citation